Perjanjian Pemborongan dengan Kontrak Unit Price pada Proyek Pemerintah dan Indikasi Persaingan Usaha Tidak Sehat di Kota Yogyakarta - Wibowo, Sigit (UIN Sunan Kalijaga Yogyakarta, 2012)
Chartering Agreement with contract unit price still new law. Unit Price termappears in a special chartering agreement for the implementation for the project forwhich payment is made after the project is handed to the government. The purpose ofthis study to know the procedure of chatering the contract unit price authors of the studythat is examining the legal aspect of normative document in determining theimplementation of the procurement of goods/ service to the payment. In this study, theimplementation of government projects implemented by chartering contract unit price, theconstruction contract (chartering) are based on the completion of all work within acertain time limit, based on the unit price of a definite and fixed for each unit/ elementwork with certain technical specifications of the volume work stil to be temporary, whilethe payment is based on the measurement results with the volume of work actually beenimplemented by service provider. Based on field, the project is the determinationchatering agreement the direct election method, as set by the Committee for theProcurement of Goods/ Services. Relation to the influence of unfair competition, thenthe chartering agreement with a contract unit price did not reveal any constructioncontract (chatering) as opposed to the existing legislation, namely Law Number5/1999 concerning Prohibition of Monopolistic Practices and Unfair BussinesCompetetion.